Empresas com CEO/Chairman fundador apresentam retorno superior ao mercado? - Silva, Guilherme Souto da (2012)
This paper shows that stock returns from firms that have CEO or Chairman as the founder of the company exceeds the return of the S&P 500 from 1995 to 2011. It’s also performed an analysis using the Fama-French 4 Factors Model and the result indicates that the portfolio has an excess risk-adjusted annualized return of 5.79% with high statistical and economic significance. The paper also proposes two additional analyses: a sector breakdown of the portfolio where it appears that the technology sector is the one that contributed the most; and a study on the portfolio’s P/E (price-earnings), which surprises by showing that the P/E is systematically higher than the P/E of the S&P 500.